MODELAGEM E VISUALIZAÇÃO DE TRINCAS 2D USANDO EQUAÇÃO INTEGRAL DE CONTORNO DUAL (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The stress analysis structures with complex geometry where it is continuously amended by the crack growth, as in aircraft fuselages, usually requires the employment of numerical methods, since the presence of cracks in the structure raises difficulties for the modelling and, therefore, the calculation of the stress intensity factors. Therefore, both the finite element method (FEM) and the boundary element method (BEM) have been applied in this type of analysis, with a slight advantage for the BEM due it does not require continuous remeshing, whenever the crack spreads. Here, the BEM will be used in the treatment of modelling crack considering two independent boundary integral equations, known as dual boundary element method (DBEM): the displacement equation applied for collocation on one of the crack boundary and remaining boundaries, and the traction equation applied for collocation on the opposite crack boundary. Moreover, boundary continuous and discontinuous quadratic elements are used, respectively, along the remaining boundaries of the problem domain and crack boundaries. Aiming to attest the efficiency and robustness of the method, a C++ program for treating cracks two-dimensional models with MATLAB interface for propagation path preview, as well as two applications of open literature, are used.